2004
DOI: 10.1177/0022487103260069
|View full text |Cite
|
Sign up to set email alerts
|

Reflecting on Elementary Children’s Understanding of History and Social Studies

Abstract: Beginning teachers in Northern Ireland and the United States conducted structured inquiry projects in which they investigated elementary children's understanding of history and social studies. Interviews with the teachers and analysis of their written assignments indicate that these investigations challenged their beliefs about children's prior knowledge and their own instructional techniques. Teachers initially believed that inadequate cognitive development and lack of backgroundknowledge limited children's a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 25 publications
1
5
0
1
Order By: Relevance
“…This study supports descriptions of pre-service and practicing teachers who believe in the capabilities of students (Grant, 2003) and use knowledge of their students to identify areas that challenge students and then design effective lessons that help everyone be successful (Monte-Sano & Cochran, 2009). Ample evidence exists that students can think historically and participate actively (Barton & Levstik, 2004;Barton, McCully, & Marks, 2004;Brophy & VanSledright, 1997;VanSledright, 2002aVanSledright, , 2002b, especially students with disabilities (Espin et al, 2007;Okolo, Englert, Bouck, & Heutsche, 2007;Okolo, Ferretti, & MacArthur, 2007), and the four teachers in this study contribute to the literature of such descriptions. Four teachers demonstrated strong curriculum consonance (Thornton, 1988) and confirmed descriptions in literature of experienced secondary social studies teachers who can clearly articulate their beliefs are more likely to implement them (Evans, 1990;Fickel, 2000;Goodman & Adler, 1985;Grant, 2003;Thornton, 1988) and adds to the literature with a description of elementary social studies teaching.…”
Section: Grounding the Findings In Literaturesupporting
confidence: 72%
“…This study supports descriptions of pre-service and practicing teachers who believe in the capabilities of students (Grant, 2003) and use knowledge of their students to identify areas that challenge students and then design effective lessons that help everyone be successful (Monte-Sano & Cochran, 2009). Ample evidence exists that students can think historically and participate actively (Barton & Levstik, 2004;Barton, McCully, & Marks, 2004;Brophy & VanSledright, 1997;VanSledright, 2002aVanSledright, , 2002b, especially students with disabilities (Espin et al, 2007;Okolo, Englert, Bouck, & Heutsche, 2007;Okolo, Ferretti, & MacArthur, 2007), and the four teachers in this study contribute to the literature of such descriptions. Four teachers demonstrated strong curriculum consonance (Thornton, 1988) and confirmed descriptions in literature of experienced secondary social studies teachers who can clearly articulate their beliefs are more likely to implement them (Evans, 1990;Fickel, 2000;Goodman & Adler, 1985;Grant, 2003;Thornton, 1988) and adds to the literature with a description of elementary social studies teaching.…”
Section: Grounding the Findings In Literaturesupporting
confidence: 72%
“…EdTPA). Still, research has shown there are connections between how preservice teachers think, about what they teach, and about how they teach history (Barton, McCully, & Marks, 2004;Evans, 1989;Hicks, 2005;Monte-Sano, 2011;Monte-Sano & Cochran, 2009;Seixas, 1998;van Hover & Yeager, 2004). In particular, Hicks (2005) found there is a clash between the ideals a pre-service teacher enters the classroom with and the reality they experience within the classroom.…”
Section: Historical Concepts and Pre-service Teachers Understandings ...mentioning
confidence: 99%
“…In a similar action research study set in a social studies methods course, Hyland and Noffke (2005) examined "how to better prepare teacher education students to successfully teach students from historically marginalized groups" (p. 367). Another group of social studies teacher educators, Barton, McCully, and Marks (2004), compared the development of inquiry among preservice social studies teachers in Ireland and the United States. These examples all positioned the methods instructor in the role of teacher researcher.…”
Section: The Social Studies and Teacher Researchmentioning
confidence: 99%